International Variation and Trends of Intraventricular Hemorrhage in Very Preterm Infants - Hollens, Georgia; Schindler, Tim; Battin, Malcolm; Klinger, Gil; Adams, Mark; Vento, Maximo; Santacroce, Antonino; Hakansson, Stellan; Isayama, Tetsuya; Norman, Mikael; Kusuda, Satoshi; Lehtonen, Liisa; et al. (S. Karger AG, 2026)
Introduction: We aimed to investigate international variation in gestational age (GA) specific severe intraventricular hemorrhage (IVH) rates, among infants of <30 weeks' GA from the neonatal networks of 11 high-income countries/region.
Methods: Retrospective cohort study of outcomes of grade 3/4 IVH rates and composite of g3/4 IVH or death in GA groups of 22-23, 24-25, 26-27, and 28-29 weeks infants admitted to networks of Australia and New Zealand, Canada, Finland, Israel, Italy (Tuscany), Japan, Spain, Sweden, Switzerland, and the UK. Their risk adjusted trends across 3 epochs (2007-11, 2012-15, and 2016-19) were also evaluated.
Results: Outcomes of 165,329 infants (median GA 27 weeks, birthweight 950 g) were analyzed. Overall, the lowest grade 3/4 IVH rate was observed in Japan (6.4%) and the highest in Israel (16.1%). The overall gestation-specific rate of IVH grade 3/4 were 25.8%, 18.6%, 9.0%, and 3.8% and composite outcome of grade 3/4 IVH/death rates 52.2%, 33.6%, 15.6%, and 6.7% for the 22-23, 24-25, 26-27, and 28-29 weeks' GA groups, respectively. These inter-network variations were greater at lower GA. In epoch comparisons, almost all networks showed significant decreases in GA specific composite outcome rates, particularly in the 26-27 week' GA group. Japan and Canada demonstrated significant decreases in each GA group while Spain demonstrated significant decreases in each GA group except for 22-23 weeks' gestation.
Conclusions: Rates of grade 3/4 IVH and composite outcome rates varied internationally and have decreased over time. Identification of the driving factors behind variations may allow for opportunities for practice review and improvement.